Low-grade inflammatory parameters may be associated with recent suicide attempts – a naturalistic study among psychiatric inpatients with depressive disorders - Lovig, Csenge; Osvath, Peter; Saghy, Eszter; Molnar, Csilla; Kovacs, Marton Aron; Petho, Borbala; Simon, Diana; Fekete, Sandor; Tenyi, Tamas; Voros, Viktor (Frontiers in Psychiatry, 2026)
IntroductionPsycho-neuro-immunological research examines the relationship between mental disorders and immune abnormalities. Chronic, low-grade inflammation was found to be associated with depression and suicidal behavior; however findings are inconsistent due to methodological differences. This study aims to identify peripheral immunological parameters that may characterize patients with recent suicide attempt.Method100 psychiatric in-patients treated with depressive disorders with or without recent suicide attempt were investigated. Demographic data, severity of depression, suicide risk and peripheral immunological parameters were recorded. Descriptive statistics and logistic regression analyses were carried out to assess differences between the recent suicide attempter and the non-suicidal groups.ResultsThere were no significant differences between recent and non-recent suicide attempters in age, gender, or depression severity. However, recent suicide attempters exhibited higher levels of leukocytes, neutrophils, eosinophils, monocytes, Neutrophil-to-Lymphocyte Ratio (NLR) and Monocyte-to-Lymphocyte Ratio (MLR). NLR and MLR remained elevated in the recent suicide attempter group after adjusting for confounders. Significant positive correlations were observed between NLR, MLR, Platelet-to-Lymphocyte Ratio (PLR), and platelet values, but not with CRP, while depression scores correlated negatively with PLR, NLR, and MLR.ConclusionAlthough elevated low-grade inflammatory parameters, particularly NLR and MLR, were observed in depressed patients with a recent suicide attempt, this study does not provide conclusive evidence for a direct association between suicide attempts and the investigated immune markers. Further research is needed to clarify this relationship between low-grade immune parameters and acute suicide attempts, to elucidate potential causal mechanisms, and to determine their relevance and clinical applicability as biomarkers of suicidal behavior.